Birth asphyxia and associated factors among newborns delivered in Jimma zone public hospitals, Southwest Ethiopia: A cross-sectional study - zelalem wayessa; Tefera Belachew; Jophin Joseph (Mashhad University of Medical Sciences, 2018)
Background & aim: Birth asphyxia is a serious clinical problem and a leading cause of neonatal mortality and morbidity worldwide. The majority of neonatal deaths arise in low- and middle-income countries. We sought to address birth asphyxia and its associated factors among newborns delivered in Jimma zone public hospitals, Southwest Ethiopia. Methods: A cross-sectional study was conducted on 368 live newborns born at Jimma zone public hospitals, who were enrolled in the study using the systematic random sampling method. Data were collected using a structured questionnaire, an observation checklist, and chart review, which were designed to measure the birth asphyxia and its associated factors. Overall, The data were analyzed using simple and multivariable logistic regression. Results: The prevalence of birth asphyxia was 32.9% in the first and 12.5% in the fifth minute. Accordingly, birth asphyxia was significantly associated with medical complications (AOR: 3.92, 95%CI: 1.62, 9.46), obstetric complications (AOR: 3.76, 95%CI: 1.71, 8.26), prolonged second stage of labor (> 3 h; AOR: 3.72, 95%CI: 1.46, 12.18), low birth weight (AOR: 4.21, 95%CI: 1.5, 12.2), meconium-stained amniotic fluid (AOR: 8.29, 95%CI: 3.6, 18.9), tight nuchal cord (AOR: 7.4, 95%CI: 1.6, 34.1), not attending antenatal care (AOR: 6.4, 95%CI: 2, 20.2), incomplete antenatal care visit (AOR: 4.6, 95%CI: 2.0, 10.5), non-cephalic presentation (AOR: 6.98, 95%CI: 2.66, 18.28), and caesarian section delivery (AOR: 2.3, 95%CI: 1.0, 5.1). Conclusion: Most factors associated with birth asphyxia are manageable by means of good pre-natal care and improving antenatal, intrapartum, and neonatal care services within our limited resources.